Bacteriophages against Serratia as Fish Spoilage Control Technology - Hernández, Igor (Frontiers in Microbiology, 2017)
Bacteria of the genus Serratia, mainly S. proteamaculans and S. fonticola, are important spoilage agents in Atlantic horse mackerel (Trachurus trachurus). In order to evaluate whether bacteriophages against Serratia could delay the spoilage process, eleven viral strains active against this genus were isolated from food and best candidate was applied to fresh mackerel fillets. All the phages belong to the Siphoviridae and Podoviridae families and were active at Multiplicity of Infection (MOI) levels below 1:1 in broth. The ability of phage AZT6 to control Serratia populations in real food was tested in Atlantic horse mackerel extract and applied to fresh mackerel fillets. Treatment with high phage concentration (MOI 350:1, initial Serratia population 3.9 ± 0.3 Log cfu/g) can reduce Serratia populations up to 90% during fish storage (a maximum of 6 days) at low temperatures (6ºC). Bacterial inhibition was dependent on the bacteriophage dosage, and MOI of 10:1 or lower did not significantly affect Serratia populations.